Characteristics of Influenza A/H1N1 complications: ARDS, pneumonia, acute kidney failure, sepsis - review - Kacper Lee; Jakub Skrzypek; Jagoda Niewiadomska; Aleksandra Stępień; Alicja Paluch; Borys Bondos; Aleksandra Niekra; Łukasz Fussek; Robert Kochan; Ewelina Wieczorek (Journal of Education, Health and Sport)
Type A h1n1 influenza got its start in 2009 during a pandemic that swept across many countries and contributed to massive mortality. It was characterised by its prevalence among young adults and children.